Glyphosate as a tool to produce shikimic acid in plants - Matallo,M.B. (2014)
Oseltamivir phosphate is a potent viral inhibitor produced from shikimic acid extracted from seeds of Ilicium verum, the most important natural source. With the site of action 5-enolpyruvylshikimate-3-phosphate synthase (EPSP), glyphosate is the only compound capable of inhibiting its activity with the consequent accumulation of shikimic acid in plants. Corn and soybean plants were sprayed with reduced rates of glyphosate (0.0 to 230.4 g a.i. ha¹) and shikimic acid content in the dry mass was determined by HPLC 3, 7 and 10 days after application. Results showed shikimic acid accumulation in dry mass with increases of up to 969% in corn and 33,000% on soybeans, with peak concentrations 3 days after treatment (DAT). Industrial feasibility for shikimic acid production, combined with favorable climatic conditions for growing corn and soybean in virtually all over Brazil, favor the use of reduced rates of glyphosate in shikimic acid biosynthesis, with potential for use as an inducer in exploration of alternative sources for production of oseltamivir phosphate with low environmental impact.